Multi-copy venom genes hidden in de novo transcriptome assemblies, a cautionary tale with the snakelocks sea anemone Anemonia sulcata (Pennant, 1977). (15th December 2015) - Macrander, Jason; Broe, Michael; Daly, Marymegan
Abstract: Using a partial transcriptome of the snakelocks anemone ( Anemonia sulcata ) we identify toxin gene candidates that were incorrectly assembled into several Trinity components. Our approach recovers hidden diversity found within some toxin gene families that would otherwise go undetected when using Trinity, a widely used program for venom-focused transcriptome reconstructions. Unidentified hidden transcripts may significantly impact conclusions made regarding venom composition (or other multi-copy conserved genes) when using Trinity or other de novo assembly programs. Highlights: We identify several sea anemone venom genes from a de novo assembled transcriptome of Anemonia sulcata . Mapping raw reads revealed consistent nucleotide polymorphisms that were used to then identify hidden toxin transcripts. The number of hidden transcripts and amount of nucleotide diversity varies considerably for all of the focal toxin types. These hidden transcripts may contain biological and functional information that typically go unnoticed.